Off-Label Use of a Double-Layer Micromesh Carotid Stent for Hybrid Treatment of Popliteal Artery Aneurism Complicated by Chronic Distal Embolization - Sorin Barat; Dumitru Casian (Case Reports in Vascular Medicine, 2021)
We report our initial experience in off-label use of the double-layer micromesh (DLM) Roadsaver® stent for the hybrid treatment of a fusiform popliteal artery aneurism complicated by distal embolization and chronic limb threatening ischemia in a COVID-19-positive young male. A 36-year-old male patient was admitted with chronic limb threatening ischemia of the left lower limb. The duplex ultrasound and computer tomography angiography (CTA) demonstrated a fusiform popliteal artery aneurism with a maximal diameter of 14 mm and distal occlusion of peroneal and both tibial arteries. Urgent hybrid intervention was performed, starting with an open thrombectomy from the distal posterior tibial artery via a retromalleolar access followed by percutaneous deployment of the DLM Roadsaver® stent (Terumo, Tokyo, Japan) for the exclusion of the popliteal artery aneurism. The flow diverting effect was observed immediately with contrast stagnation in the asymmetrical part of the aneurism sac (grade C2 of the O’Kelly-Marotta flow diversion scale). The procedure was uneventful, with the regaining of an adequate foot perfusion and palpable pulse at the posterior tibial artery. On the 2nd postoperative day, the patient was diagnosed with a symptomatic form of COVID-19 infection and transferred to a dedicated facility. At a one-month follow-up, the patient had no symptoms of limb ischemia and CTA showed complete thrombosis of the aneurism sac, absence of endoleaks, and patency of the treated arterial segment. This case demonstrates the possibility of off-label use of the DLM Roadsaver® stent for hybrid treatment of popliteal artery aneurism complicated by distal embolization and critical limb ischemia.